Performance of hydrogen direct injection engine - Abdul Aziz, A.R. (2019)
Hydrogenâs high flammability, low ignition energy, clean burning, and high flame speed are attractive advantages of using internal combustion engines to attain high performance and efficiency as well as achieving ârealâ clean emission with only water and carbon dioxide as exhaust. To overcome volumetric efficiency loss, high NOx emissions and abnormal combustion, the influence of airâfuel ratio is studied. Optimization of the airâfuel ratio effect and understanding of the combustion processes are actively being studied in the automotive industry and research institutions. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2019.